PENGARUH PENAMBAHAN ADSORBEN DAN KULTUR BAKTERI TERHADAP KARAKTERISTIK FESES AYAM RAS PEDAGING - Cokorda Mahardika; Wely Yitro Pello; Yohan Nenomnanu (Partner, 2022)
This study was conducted to investigate the effect of adding adsorbents and cultur bacteria in feces to characteristic of chicken excreta. For each treatment-replication, 150 g of fecal material were collected from the poultry farm and placed in beaker glass. The fecal sample was then treated with 8% activated nature zeolite, 8% carbon active, and 8% bacterial culture Effective Microorganism-4TM and covered with plastic wraps. The temperature and pH were measured after one hour of standing (0 d) and repeated at 48 h intervals for 8 days. Moisture content were measured after one hour of standing (0 d) and 192 hour after incubation. Results indicated that adsorbents with 8% activated nature zeolite, carbon active, and culture bacteria each can reduced the moisture content. The adsorbents had no significant effect on pH and temperature of fecal broilers.Key words:  Adsorbents, fecal material, moisture, pH, temperature